DETERMINASI AKUNTABILITAS PENGELOLAAN DANA DESA (Studi Kasus di Kecamatan Ngombol Kabupaten Purworejo) - Prasetyani, Meiliana; Kusumawati, Eny (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine the effect of transparency, community participation, competency of village apparatus, internal control structure and effectiveness on accountability of village funds manaagement in Ngombol District, Purworejo Regency, Central Java. This study uses a quantitative approach, for the process of collecting data used the questionnaire method. The population used is all village officials involved in budgeting village funds, namely: Village Head, Village Treasurer, and Village Consultative Body in 53 villages in Ngombol District, Purworejo Regency with a total of 159 respondents. The analytical method used is multiple regression analysis. The results of the study show that transparency, internal control structure, and effectiveness influence the accountability of village fund management. Meanwhile, community participation and the competence of village officials have no effect on the accountability of village fund management. Keywords: Accountability of Village Funds Management, Transparency, Community Participation, Village Apparatus Competence, Internal Control Structure, Effectiveness